Towards optimizing canal system operations: Extremum-seeking controller design via a frequency-based control approach - Ucun, Buse Tacal; Engin, Seref Naci (ELSEVIER, 2024)
This paper addresses strategies for enhancing the operational management of canal systems, aiming to reduce water losses resulting from overflows that arise due to inadequate water level control during canal operations. The study focuses on nonlinear modeling and system identification of a canal system, presenting a detailed analysis, design, and practical implementation of a frequency-based compensator. The mathematical model of the experimental canal system is derived through real-time experiments. The operational management of this experimental canal system is achieved using a compensator structure based on Bernstein polynomials. The proposed compensator parameters are refined using the extremum-seeking control algorithm, which is employed for optimizing a frequency-based cost function. The efficiency and performance of the proposed compensator compared to the cases where classical PI and two-degree-of-freedom PI with feed-forward controllers are used demonstrated through time domain and harmonic analysis plots related to the water level dynamics.
Keywords: Canal system; Extremum-seeking control; Describing functions; System identification; PREDICTIVE CONTROL; FRICTION COMPENSATION; NONLINEAR-SYSTEMS; IRRIGATION; MODEL; IDENTIFICATION; Engineering